A new species of Syringogastridae (Diptera, Acalyptratae) from the Amazon Basin and new records for Brazil - Rafael, J. A.; Câmara, J. T.; Holanda, M. J. A. (Zootaxa, 2011)
Syringogaster papaveroi Prado, 1969 is redescribed from southeastern Brazil, and S. fapeam, n. sp., is described from the upper Rio Negro, state of Amazonas. The known range of S. apiculata Marshall and Buck, 2009, previously known from Amazonian Peru and Ecuador, is extended for the first time to Brazil. The phylogenetic tree and key of Marshall et al., 2009 are emended to include the new species and new information on S. papaveroi.